Effect of la on the structure and characteristics of multiferroic BiFeO3 - Lam, Dao Son; Linh, Dinh Chi; Bach, Ta Ngoc; Dung, Dang Duc; Huong, Ngo Thu; Thanh, Tran Dang (Vietnam Journal of Science and Technology, 2022)
Bi1-xLaxFeO3 (x = 0, 0.1, 0.2, 0.3) ceramics with a particle size of about 100 nm were prepared by high energy ball milling method and annealed at 800 oC in air for 6 h. Effects of La substitution on the structural, magnetic, ferroelectric, and optical properties of BiFeO3 were examined in detail and systematically. The results indicate that partial replacement of Bi3+ by La3+ contributes to the formation of hexagonal single phase. Due to the increase of La3+ ion content, the values of the remnant polarization (Pr) and the coercive field (Ec) are improved, the maximum values achieved is about 0.0036 µC/cm2 and 0.57 kV/cm, respectively, for sample x = 0.2. For increasing La doped content in BiFeO3, the value of coercivity magnetic field (Hc) tends to decrease gradually. The optical property of Bi1-xLaxFeO3 ceramics was studied by analyzing their UV-vis absorption spectra. The value of band gap energy (Eg) of materials decreases from 1.86 to 1.78 eV, corresponding to x = 0 - 0.2, and the broad absorption band in the wavelength range of 660-700 nm. The observed characteristics of La-doped BiFeO3 may be helpful for the further search for high-performance lead-free multiferroic magnetoelectric materials, oriented toward applications in solar cells, optoelectronic devices, or in the environmental pollution treatment technology field by the photocatalytic reaction.